2000
DOI: 10.1002/1096-9888(200006)35:6<725::aid-jms1>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-assisted laser desorption/ionization mass spectrometric quantification of the mu opioid receptor agonist DAMGO in ovine plasma

Abstract: The synthetic opioid peptide analog Tyr-D-Ala-Gly-N-methyl-Phe-Gly-ol (DAMGO), which is a mu opioid receptor-selective agonist, was quantified in ovine plasma samples with matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOFMS), using delayed extraction and a reflectron. The internal standard was pentadeuterated DAMGO. Timed-ion selection was used to select the precursor ion. The analysis of the post-source decay fragments improved the detection sensitivity, and the use of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In the cases examined, the two peptides were of similar molecular mass (1385.56 versus 1046.48 Da) but of different composition. Several studies reported the use of structural analogues (8,22), derivatives (8,10,11,19), functional analogues (9), molecules of similar hydrophobicity (12), or isotopically labeled derivatives (5,6,8,11) of the analyte as internal standards. Some of these have indeed published calibration lines with quite small mean relative standard deviations (6,12).…”
Section: Examining the Correlation Between The Relative Signal Intensmentioning
confidence: 85%
See 1 more Smart Citation
“…In the cases examined, the two peptides were of similar molecular mass (1385.56 versus 1046.48 Da) but of different composition. Several studies reported the use of structural analogues (8,22), derivatives (8,10,11,19), functional analogues (9), molecules of similar hydrophobicity (12), or isotopically labeled derivatives (5,6,8,11) of the analyte as internal standards. Some of these have indeed published calibration lines with quite small mean relative standard deviations (6,12).…”
Section: Examining the Correlation Between The Relative Signal Intensmentioning
confidence: 85%
“…Lately MALDI-TOF MS has become a popular method for quantitative analysis of biomolecules (oligonucleotides, proteins, glycoproteins, etc.) originating from various sample types (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) or even for imaging tissue sections (13)(14)(15)(16)(17)(18)(23)(24)(25)(26). At the same time, several studies discuss the non-quantitative nature of MALDI-TOF MS (7, 8, 13, 19, 22, 26 -30).…”
mentioning
confidence: 85%
“…More recently developed methods such as quantitative matrix-assisted laser-desorption/ ionization-mass spectrometric (MALDI-MS) approaches [46,47,48,49,50] or surface-enhanced laser desorption/ionization (SELDI) technologies [16,51,52] have been discussed in the literature. In general, most of the immunological methods are characterized by low limits of detection (pico-to femtomolar concentrations), high sample throughput, high sensitivity and selectivity.…”
Section: Methods For Peptide Quantificationmentioning
confidence: 99%
“…Compared with other available techniques, this method affords advantages in specificity and sensitivity for angiotensin peptide detection (37,38). After chronic Ang II infusion, we find that renal Ang II levels are more than 5-fold higher in ACE2-deficient mice than in controls, indicating that the more severe hypertension in ACE2-deficient mice is due to impaired metabolism of Ang II in the kidney.…”
Section: Figurementioning
confidence: 99%